CLASSIFICATION AND DECISION OF RSPO CERTIFICATION ADOPTION: AN EMPIRICAL EVIDENCE FROM OIL PALM SMALLHOLDERS IN OGAN KOMERING ULU - Yulia Sari; Dian Amalina; Dessy Adriani; Khairul Fahmi Purba; Merna Ayu Sulastri; Rika Miliana; Muhammad (LPPM Universitas Malikussaleh - Indonesia, 2026)
This study aims to analyse the adoption process, identify adopter categories, and examine the factors influencing smallholder oil palm farmers’ decisions to adopt Roundtable on Sustainable Palm Oil (RSPO) certification in Penilikan Village. RSPO certification plays an important role in promoting sustainability in the oil palm sector, however participation remains limited. This study eused a survey method involving 70 respondents, consisting of 35 RSPO-certified farmers and 35 non-certified farmers selected through stratified sampling. Descriptive analysis was used to assess the adoption process and adopter categories, binary logistic regression was applied to analyse the determinants of adoption decisions. The results revealed that most farmers were at the confirmation stage of adoption (41.43%), indicating a process of re-evaluating adoption decisions. 40% of respondents were classified as late majority adopters, reflecting cautious and slow adoption behaviour. All independent variables significantly influenced adoption decisions, while partially only access to information showed a significant effect. Farmers with better access to information were 5.107 times more likely to adopt RSPO certification. The study concludes that access to information is the key determinant of RSPO certification adoption among smallholder oil palm farmers. Therefore, strengthening farmer participation in training and extension activities related to RSPO certification is recommended. Keywords: Acess Information, Adopter Category, Adoption Process, RSPO Certification, The People’s Oil Palm Farmers